VALIDITAS MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR DI SEKOLAH MENENGAH KEJURUAN - Radinal Fadli; Muhammad Hakiki; Suci Rahayu; Serly Astriyani (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2020)
Based on observations implementation of learning computer and basic network indicated only limited by using print module media, with lecture methods and guided practice and have not used learning media with android technology. This research purpose to obtain validity of learning media android-based on computer and basic network subjects. Interactive learning media based on android is designed to improve students' understanding so as to improve learning outcomes. This research is a Research and Development (R and D) with 4-D method development procedures (Define, Design, Develop, Desseminate). Data analysis techniques used descriptive analysis techniques to describe the validity of interactive learning media android-based. The results obtained from this development research the validity of Android-based interactive learning media is declared valid on the media aspects and material aspects. Based on the result of this reserch concluded that the interactive learning media android- based was declared valid to be used as teaching materials in computer and basic network.